Detection of brain lesions after catheter ablation depends on imaging criteria: insights from AXAFA-AFNET 5 trial - Haeusler, Karl Georg; Eichner, Felizitas A.; Heuschmann, Peter U.; Fiebach, Jochen B.; Engelhorn, Tobias; Callans, David; De Potter, Tom; Debruyne, Philippe; Scherr, Daniel; Hindricks, Gerhard; Al-Khalidi, Hussein R.; Mont, Lluis; et al. (Europace, 2023)
Aims Left atrial catheter ablation is well established in patients with symptomatic atrial fibrillation (AF) but associated with risk of embolism to the brain. The present analysis aims to assess the impact of diffusion-weighted imaging (DWI) slice thickness on the rate of magnetic resonance imaging (MRI)–detected ischaemic brain lesions after ablation. Methods AXAFA-AFNET 5 trial (NCT02227550) participants underwent MRI using high-resolution (hr) DWI (slice thickness: and results 2.5–3 mm) and standard DWI (slice thickness: 5–6 mm) within 3–48 h after ablation. In 321 patients with analysable brain MRI (mean age 64 years, 33% female, median CHA2DS2-VASc 2), hrDWI detected at least one acute brain lesion in 84 (26.2%) patients and standard DWI in 60 (18.7%; P < 0.01) patients. High-resolution diffusion-weighted imaging detected more lesions compared to standard DWI (165 vs. 104; P < 0.01). The degree of agreement for lesion confirmation using hrDWI vs. standard DWI was substantial (κ = 0769). Comparing the proportion of DWI-detected lesions, lesion distribution, and total lesion volume per patient, there was no difference in the cohort of participants undergoing MRI at 1.5 T (n = 52) vs. 3 T (n = 269). Conclusion The pre-specified AXAFA-AFNET 5 sub-analysis revealed significantly increased rates of MRI-detected acute brain lesions using hrDWI instead of standard DWI in AF patients undergoing ablation. In comparison to DWI slice thickness, MRI field strength had a no significant impact in the trial. Comparing the varying rates of ablation-related MRI-detected brain lesions across previous studies has to consider these technical parameters. Future studies should use hrDWI, as feasibility was demonstrated in the multicentre AXAFA-AFNET 5 trial.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Ablation; Brain MRI; Diffusion-weighted imaging; Field strengths; Slice thickness